The glutathione S-transferase P1 341C>T polymorphism and cancer risk: a meta-analysis of 28 case-control studies. - Sheng-xin Huang; Fei-xiang Wu; Min Luo; Liang Ma; Ke-feng Gao; Jian Li; Wen-juan Wu; Shan Huang; Qi Yang; Ke Liu; Yin-nong Zhao; Le-qun Li (PLoS ONE, 2013)
BACKGROUND: GSTP1, which is one major group of the glutathione S-transferase family, plays an important role in the metabolism of carcinogens and toxins, reducing damage of DNA as a suppressor of carcinogenesis. The 341C>T polymorphism of the GSTP1 has been implicated in cancer risk through cutting down its metabolic detoxification activities. However, results from previous studies remain conflicting rather than conclusive. To clarify the correlation and provide more statistical evidence for detecting the significance of 341C>T, a meta-analysis was conducted. METHODOLOGY/PRINCIPAL FINDINGS: The relevant studies were identified through searching of PubMed, Embase, ISI Web of Knowledge and China National Knowledge Infrastructure in August 2012, and selected based on the established inclusion criteria for publications, then a meta-analysis was performed to quantitatively summarize the association of GSTP1 341C>T polymorphism with cancer susceptibility. Stratified analyses were employed to identify the source of heterogeneity. Publication bias was evaluated as well as sensitivity analysis. Based on 28 case-control studies with 13249 cases and 16798 controls, the pooled results indicated that the variant genotypes significantly increased the risk of cancer in homozygote comparison (TT versus CC: P = 0.012, OR = 1.40, 95% CI: 1.08-1.81, P(het.) = 0.575), and recessive model (TT versus CT/CC: P = 0.012, OR = 1.40, 95% CI: 1.08-1.81, P(het.) = 0.562). This was confirmed when stratified analyses were conducted according to ethnicity, source of control, matched control, quality score and cancer types. Moreover, significantly increased risk of cancer was also found in lung cancer (heterozygote comparison and dominant model). The stability of these observations was confirmed by a sensitivity analysis. Begger's funnel plot and Egger's test did not reveal any publication bias. CONCLUSIONS/SIGNIFICANCE: This meta-analysis suggests that the GSTP1 341C>T polymorphism may contribute to genetic susceptibility to cancer, especially to lung cancer, and in Asian population. Nevertheless, additional well-designed studies focusing on different ethnicity and cancer types are needed to provide a more exact and comprehensive conclusion.